Mosaic Trisomy 21 and Trisomy 14 as Acquired Cytogenetic Abnormalities without GATA1 Mutation in A Pediatric Non-Down Syndrome Acute Megakaryoblastic Leukemia - Xiao, Yi (Springer-Verlag Berlin Heidelberg, 2011)
One case of acute megakaryoblastic leukemia (AMKL) with trisomy 21, trisomy 14 and unmutated GATA1 gene in a phenotypically normal girl was reported. The patient experienced transient myelodysplasia before the onset of AMKL. The bone marrow blasts manifested typical morphology of megakaryoblast both by the May-Giemsa staining and under the electronic microscopy. Leukemic cells were positive for CD13, CD33, CD117, CD56, CD38, CD41 and CD61 in flow cytometry analysis. Cytogenetic study showed karyotype of 48, XX, +14, +21 in 40% metaphases. Known mutations of GATA1 gene in Down syndrome or acquired trisomy 21 were not detected in this case.